Analysis on the Spindle Bearing Force of RV Reducers Based on the Fuzzy Theory—Wang Xinlong1 Pang Xiaoxu1,2,3 Qiu Ming1,2,3 Shen Wenliang<alternatives>4 <?fx-imagestate width="1.18533325" height="3.30200005"?> <?fx-imagestate width="1.18533325" height="3.30200005"?> </alternatives> - Wang Xinlong; Pang Xiaoxu; Qiu Ming; Shen Wenliang (Jixie chuandong)
Aiming at the RV reducer spindle force problem, and based on the Romax force analysis of the main bearing, it is found that due to the different magnitude and span of the impact parameters, the influence degree of each parameter on the spindle bearing force cannot be determined. Based on this, a fuzzy comprehensive evaluation method is proposed. The results show that the number of cycloidal wheel pins and the radius of cycloidal wheel pitch have the greatest influence on the force of the main bearing. The entropy weight method and grey relational degree are used to verify the influence degree of each parameter on the bearing capacity of the spindle. The results obtained by the fuzzy comprehensive evaluation method are consistent with the results obtained by the entropy weight method and grey relational analysis method, which verify the effectiveness of the fuzzy comprehensive evaluation method.